The role of the National Support Centre for Agriculture in the process of revitalization and renewal of the rural areas - Ogryzek Marek P.; Rząsa Krzysztof; Ciski Mateusz (Journal of Water and Land Development, 2019)
Rural development policy of Agricultural Property Stock (APS) of the State Treasury in Poland is run by the National Support Centre for Agriculture (until 31.08.2017 Agricultural Property Agency). In the article, on the example of the Braniewo municipality, the size and spatial distribution of land transferred from the Agricultural Property Stock (APS) of the State Treasury to the municipality was analysed. One of the most important goals associated with this was activities related to social aspects, often part of the revitalization and renewal of the rural areas. After Poland's accession to the European Union, it was possible to obtain subsidies that allowed the rural population to apply for financing projects, such as: road construction, creating school playgrounds or socio-cultural facilities. Authors also analysed examples of good practices in this area in the municipality of Braniewo, as a recommendation for other municipalities. Attempts have also been made to indicate the role of the National Support Centre for Agriculture in the transformation of the Polish countryside, with particular emphasis on the areas of former State Agricultural Farms.